Efficacy of face-to-face behavior change counseling interventions on physical activity behavior in cancer survivors – a systematic review and meta-analysis. Issue 19 (11th September 2022) - Meyer-Schwickerath, Corinna; Morawietz, Christina; Baumann, Freerk T.; Huber, Gerhard; Wiskemann, Joachim
Abstract: Purpose: This systematic review and meta-analysis of randomized controlled trials determines the efficacy of face-to-face behavior change counseling (BCC) interventions on physical activity (PA) behavior in adult cancer survivors at least pre-and immediately post-intervention compared to usual care. Additionally, this review aims to answer the question which behavior change techniques (BCTs) are most effective. Materials and methods: A structured search of the databases Medline, OTseeker, PEDro, the Cochrane Library, and article reference lists was conducted. All trials were critically appraised for methodological quality using the PEDro scale. The BCC interventions were coded using the BCT Taxonomy (v1). Random effect meta-analysis explored between group differences in PA behavior post intervention. Standardized mean differences (SMD) describe effect sizes. Results: Fourteen studies were included, 12 effect sizes within 11 trials were pooled in meta-analysis. The SMD between groups favored the intervention group with a small effect (SMD 0.22; 95% CI 0.11, 0.33; p < 0.0001). The BCTs "graded tasks", "self-monitoring of behavior", "action planning" and "habit reversal" were more frequently coded in more efficacious interventions. Conclusion: BCC interventions are effective in increasing PA behavior in cancer survivors. Further research is needed providing details of fidelity assessment and structuring the intervention description by using a BCT taxonomy. Health care professionals should consider our results while awaiting further trial evaluation. Implications for Rehabilitation: Face-to-face behavior change counseling interventions can significantly increase physical activity behavior in cancer survivors. Although small differences are evident, included trials presented with a broad variety of study components, and characteristics, which limits the interpretation of effective components. The behavior change techniques "Graded tasks", "Action planning", "Habit reversal", and "Credible Source" were used in the trials with a positive effect, but not in the ineffective ones.